Diagnosis of spatial neglect and rehabilitation access for stroke survivors - Corey Morrow; Holden Gasque; Michelle Woodbury; Eyad Almallouhi; Annie Simpson; Kit Simpson (Cogent Gerontology)
Spatial neglect in stroke survivors is associated with a decrease in quality of life. This disorder occurs in 20–80% of stroke survivors and up to 1/3 of stroke survivors will continue to experience chronic impairment. Occupational therapists are uniquely qualified to treat stroke survivors with spatial neglect due to their holistic approach but access to therapy is limited. Diagnostic coding is used to help determine appropriate reimbursement and continuation of care including rehabilitation services. The objectives of this study were to 1) identify the prevalence of diagnostic coding for spatial neglect in stroke survivors, and 2) identify the prevalence and types of rehabilitation for patients with diagnostic coding for spatial neglect. We completed a retrospective cohort analysis using 2018 and 2019 5% Medicare Limited Data Sets from the Centers for Medicare and Medicaid Services. We extracted all ischemic stroke survivors and stratified them by the presence of a secondary diagnostic code indicating spatial neglect. Rehabilitation Current Procedural Terminology codes were used to identify stroke survivors who received rehabilitation. Despite recommendations from clinical practice, only 4.9% had a diagnostic code for spatial neglect. Of those formally diagnosed, only 2.3% received outpatient occupational therapy after being discharged from acute care.